Differentiating antiepiligrin cicatricial pemphigoid from epidermolysis bullosa acquisita by indirect immunofluorescence of skin substrates lacking Type VII collagen or laminin 332: a case report and review of literature - Chih-Pin Chen; Richard Plunkett; Raminder Grover; Song-Jen Hong (Wolters Kluwer Medknow Publications, 2011)
Antiepiligrin cicatricial pemphigoid (AECP) is a chronic autoimmune subepidermal blistering disease characterized by clinical features of cicatricial pemphigoid and circulating IgG antibasement membrane autoantibodies directed against laminin 332. There is growing evidence of an increased relative risk for solid cancers and lymphomas in AECP patients, especially in the 1st year after the onset of blisters. However, it is difficult to distinguish patients with initially skin-predominant AECP from similar findings of epidermolysis bullosa acquisita merely based on clinical, histopathologic, and immuno-pathologic examinations. This is a report on a case of AECP confirmed by indirect immunofluorescence of type VII collagen- and laminin 332-deficient skin as substrates to differentiate it from epidermolysis bullosa acquisita.